1990
DOI: 10.1017/s0022215100112599
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy—The horizontal tracheal incision

Abstract: The complication rate after emergency tracheostomy is two to five times greater than after elective procedures. One of the main causes of the high risk of complications in emergency tracheostomy appears to be the amount of time required to open the trachea. Therefore, simple and fast procedures are mandatory. We have developed a new procedure as follows: A horizontal skin incision is performed. Strap muscles are dissected and retracted laterally. A transverse cut between tracheal rings below the thyroid isthmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…Indication of tracheostomy: In current study, the upper airway obstruction was the main indication for the tracheostomy (60.7%); this is due to the high incidence of laryngeal tumor in which the patient presented in advanced stage, also the high incidence of blast injury during the period of study led to the upper airway obstruction to be a main cause. The 2nd common cause of tracheostomy was when it performed as a part of other procedure for protection of the airway or due to difficult intubation, it was found in 21.3%, while prolonged ventilation as a cause for the tracheostomy was found in 18%.this results agreed with other study like, (Adeyi A Adoga, et al, 2009) 2 reported that upper airway obstruction was the commonest cause of tracheostomy it found in 63% of his patients, (Kato et al, 1990) 3 reported that airway obstruction was the predominant cause of tracheostomy found in 42%, Hussam, Rasheed, 1999 4 also reported that upper airway obstruction was the commonest indication found in 72.5% followed by tracheostomy for protection of airway in 22.5% and lastly for prolonged ventilation in 5%. Garap, J P et al, 1999 5 Reported that "the mechanical airway obstruction is the commonest cause of tracheostomy, followed by prolonged ventilation and lastly for protection of airway".…”
Section: Discussionsupporting
confidence: 82%
“…Indication of tracheostomy: In current study, the upper airway obstruction was the main indication for the tracheostomy (60.7%); this is due to the high incidence of laryngeal tumor in which the patient presented in advanced stage, also the high incidence of blast injury during the period of study led to the upper airway obstruction to be a main cause. The 2nd common cause of tracheostomy was when it performed as a part of other procedure for protection of the airway or due to difficult intubation, it was found in 21.3%, while prolonged ventilation as a cause for the tracheostomy was found in 18%.this results agreed with other study like, (Adeyi A Adoga, et al, 2009) 2 reported that upper airway obstruction was the commonest cause of tracheostomy it found in 63% of his patients, (Kato et al, 1990) 3 reported that airway obstruction was the predominant cause of tracheostomy found in 42%, Hussam, Rasheed, 1999 4 also reported that upper airway obstruction was the commonest indication found in 72.5% followed by tracheostomy for protection of airway in 22.5% and lastly for prolonged ventilation in 5%. Garap, J P et al, 1999 5 Reported that "the mechanical airway obstruction is the commonest cause of tracheostomy, followed by prolonged ventilation and lastly for protection of airway".…”
Section: Discussionsupporting
confidence: 82%
“…That's why various studies in literature are of the opinion that the frequency of the complications is higher in emergency situations as compared to elective situations and it is 3-5 times more in emergency tracheostomy. 24 In this study it also 3.66 times more in emergency than elective tracheostomy.…”
Section: Discussionsupporting
confidence: 48%
“…In the previous study carried out in our country it was found to be emergency tracheostomies 91% and elective 9% [16], another study showed that emergency 93% and 7% were elective. 24 Those results were widely varied from our study. But findings of our study was similar with other studies carried out abroad where emergency tracheostomy were found only (16% to 23%) 20,21 .…”
Section: Discussionmentioning
confidence: 66%
“…Emergency tracheostomy has two-fold complication rate than the elective, due to longer time spent isolating the trachea as a result of commonly occurring bleeding. [14] After giving incision for emergency surgical airway, we found the tip of ET tube lying outside the trachea and so, we passed a new ET tube through the distal tracheal end.…”
Section: Discussionmentioning
confidence: 99%